Dose- and Time-Dependent Effect of Dietary Blueberries on Diabetic Vasculature Is Correlated with Gut Microbial Signature - Adhini Kuppuswamy Satheesh Babu; Chrissa Petersen; Henry A. Paz; Kai Benedict; Miley Nguyen; Madison Putich; Miguel Saldivar-Gonzalez; Ying Zhong; Sydney Larsen; Umesh D. Wankhade; Pon Velayutham Anandh Babu (MDPI AG, 2023)
Evidence from our lab and others indicates the vascular effects of dietary blueberries. In the present study, we determined dietary blueberries' dose- and time-dependent effects on diabetic vasculature and their association with gut microbes. Seven-week-old db/db diabetic male mice were fed a diet supplemented with ± freeze-dried wild blueberry powder (FD-BB) for 4, 8, or 12 weeks (three cohorts). Diets contained 0%, 1.23%, 2.46%, and 3.7% of FD-BB, equivalent to 0, ½, 1, and 1.5 human servings of wild blueberries, respectively. The non-diabetic db/+ mice fed a standard diet served as controls. Metabolic parameters, vascular inflammation, and gut microbiome were assessed. Dietary supplementation of 3.7% FD-BB improved vascular inflammation in diabetic mice without improving systemic milieu in all three cohorts. Blueberries improved diabetes-induced gut dysbiosis depending on blueberry dosage and treatment duration. Spearman's correlation indicated that the opportunistic microbes and commensal microbes were positively and negatively associated with indices of vascular inflammation, respectively. Dietary blueberries reduced the opportunistic microbe that was positively associated with vascular inflammation (Desulfovibrio), and increased the commensal microbe that was negatively associated with vascular inflammation (Akkermansia). Dietary blueberries could be a potential adjunct strategy to beneficially modulate gut microbes and improve vascular complications in diabetes.